2015
DOI: 10.1155/2015/251403
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Urine Biomarkers for Human Renal Cell Carcinoma

Abstract: Renal cell carcinoma (RCC) diagnosis is mostly achieved incidentally by imaging provided for unrelated clinical reasons. The surgical management of localized tumors has reported excellent results. The therapy of advanced RCC has evolved considerably over recent years with the widespread use of the so-called “targeted therapies.” The identification of molecular markers in body fluids (e.g., sera and urine), which can be used for screening, diagnosis, follow-up, and monitoring of drug-based therapy in RCC patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 87 publications
(90 reference statements)
0
41
0
Order By: Relevance
“…Recent studies suggested that several prognostic models that were developed based on the TNM system may not effectively predict the postoperative prognosis of distinct RCC types, and the development of improved models with increased accuracy for recurrence patterns is sorely needed [10,11,12]. Additionally, diagnostic and prognostic molecular markers for RCC have not yet been fully incorporated into clinical practice [13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggested that several prognostic models that were developed based on the TNM system may not effectively predict the postoperative prognosis of distinct RCC types, and the development of improved models with increased accuracy for recurrence patterns is sorely needed [10,11,12]. Additionally, diagnostic and prognostic molecular markers for RCC have not yet been fully incorporated into clinical practice [13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…Obviously, biomarkers presented in blood are preferable than markers obtained from other tissues. For this purpose, many attempts have been performed aimed at recognizing novel informative RCC biomarkers applicable for early detection of the disease and a number of serological markers including VEGF, TATI have been reported to have diagnostic potential for early RCC [8,9]. However, their efficiency remains quite different and insufficient in sensitivity and/or specificity have limited their clinical feasibility.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the findings of routine diagnostic blood tests might be altered by RCC, but no change is pathognomonic. In addition, although several serum proteins have been ported to be able to detect the presence of advanced or recurrent RCC, unfortunately, none are used in the routine practice because they do not improve the diagnostic or prognostic accuracy [8,9]. Thus, there is an urgent need for the development new serum biomarkers and further introduction into clinical practice for RCC detection and monitoring, and in particular, accurate early diagnostic tools for RCC to obtain better treatment results.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of molecular markers in body fluids (e.g., sera and urine), which can be used as noninvasive diagnostic, prognostic and surveillance markers in ccRCC management, is one of the most ambitious challenges in oncologic research [20]. Of note, also miRNAs are acquiring a great potential as novel cancer biomarkers in urological carcinomas [16,[21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%